INSECT AND NON-INSECT PESTS INFESTING POINTED GOURD (TRICHOSANTHES DIOICA ROXB.) IN WEST BENGAL - BARMA, PRANAB; SHANTANU JHA (The Bioscan, 2013)
Pointed gourd (Trichosanthes dioica Roxb.) was found to be infested by seven insect and non-insect pests viz. Epilachna dodecastigma (Wied.), Aulacophora foveicollis (Lucas),Diaphania indica(Saunders), Bactrocera cucurbitae (Coquillett), Bemisia tabaci (Gennandius), Tetranychus urticae (Koch) and Meloidogyne incognita (Kofoid and White). Peak incidences of mite in last week of April to first fortnight of May, of leaf roller in third week of January, first to second week of March, first to second week of April, first fortnight of May, first week of June, second week of July, of fruit fly usually, in third week of May to first week of June and that of epilachna beetle in March, first fortnight of April, May, third week of July were obtained. Maximum temperature, morning and evening RH% and bright sun shine hour (BSS) had significant association on the mite population. Max temp., min temp., morning RH%, evening RH%, rainfall, soil temperature and BSS had significant association with leaf roller population. Max temp., min temp., morning RH% and soil temperature had significant association with fruit fly population. Max temp., morning RH%, evening RH%, rainfall and BSS had significant association with epilachna population.